A solution approach to the weak linear bilevel programming problems. (2nd July 2016) - Zheng, Yue; Fang, Debin; Wan, Zhongping
Abstract : In this paper, we study the weak linear bilevel programming problems. For such problems, under some conditions, we first conclude that there exists a solution which is a vertex of the constraint region. Based on the classical K th-Best algorithm, we then present a solution approach. Finally, an illustrative example shows that the proposed approach is feasible.